Women’s health and healthcare experiences in the years after gestational diabetes or hypertensive disorders of pregnancy - Bec Jenkinson; Valerie Charlton; Leah Hardiman; Ayme Limmer; Melanie McKenzie; Anna-Lee Ura; Carissa Bonner; Sheleigh Lawler; Philippa Middleton; Gita Mishra; Jenny Doust (BMC Pregnancy and Childbirth)
Abstract Background Pregnancy complications, such as gestational diabetes mellitus (GDM) and hypertensive disorders of pregnancy (HDP), affect a significant proportion of women in Australia, with long-term implications for cardiovascular disease (CVD) risk. Despite existing preventive measures, participation in ongoing health monitoring remains low. This study aims to explore women’s preferences and experiences regarding preventive healthcare after GDM and HDP, and to identify their unanswered questions about the association between these conditions and future CVD risk. Methods A participatory, qualitative approach was adopted, involving a Lived Experience Expert Group (LEE Group) to plan, conduct, and interpret focus groups with women who had experienced either GDM or HDP. Participants were recruited through health consumer and community organisations and took part in two focus groups conducted via Zoom. The focus groups involved a stimulus presentation about CVD and GDM or HDP, facilitated group discussion about participants’ health and healthcare since their pregnancy, and Nominal Group Technique to prioritise participants’ questions about their CVD risk. Focus groups were audio recorded and transcripts from each group were analysed thematically. Synthesised Member Checking was used to verify the trustworthiness of findings. Results Twelve women participated in the focus groups, with distinct themes emerging from the GDM and HDP focus groups. Participants were previously unaware of the association between their pregnancy complication and increased risk of future CVD and wished to know more. Three themes were generated from the GDM focus groups: ‘a distressing diagnosis’; ‘degrees of diabetes’; and ‘balancing motherhood and self-care’. Two themes were generated from the HDP focus groups: ‘women’s concerns were dismissed’ and ‘wanting follow up at the right time and with the right person’. The ‘top ten’ questions from each group focussed on improving maternity care, preventing CVD, and (for the HDP group) concerns beyond CVD. Conclusions Women’s capacity to engage in preventive health after GDM and HDP is influenced by their maternity care experiences and the accessibility of primary care pathways. Future interventions should focus on improving woman-centred maternity care, ensuring seamless transitions to primary care, and addressing the social determinants of health for new mothers.